Adsorptive Removal Of Phenol And P-Chlorophenol By Activated Carbons. - Kamaludin, Hafizah (2004)
In this study, two kinds of commercial activated carbons (Calgon Filtrasorb 400 Activated Carbons & Coconut Shell-Based Activated Carbons) were used for adsorption of phenols from contaminated water.